Frozen Meat Sales Website Design Based on Laravel Framework - Meri Mayang Sari; Lily Wijaya; Fitria Supyaningsih (Universitas Raharja, 2023)
To market a product is usually done by offering it to many people you meet or giving brochures. However, if a product that is sold and offered to potential buyers is not everyone's consumptive product, then the marketing must be different. The use of digital media in the current technological era, it is highly recommended to market products as a means of selling such as a sales website . Sales transactions made at the company so far are conventional, such as ordering products using telephone media and sales that come directly to stores and offer products. Management of data and reports is still done semi-computerized using Microsoft Office. The purpose of this study is to analyze the problems that occur and provide system design proposals for the company. Data collection techniques were carried out by means of observation, interviews, and literature study. method of analysis in this study using PIECES analysis. To describe the design model and system design using Unified Modeling Languages (UML). The result of this research is a sales information system designed using the PHP programming language, database MySQL, and assisted by frameworks such as laravel. With this proposed system, it will be easier for customers to find and buy products contained in the company as a company's sales promotion media, and assist sales in selling products.